Peran Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan di Dinas Damkar Kota Bandar Lampung - Putri, Ramadania Novita (Gorontalo State University, 2025)
This study aims to analyze the role of transformational leadership style on employee performance at the Bandar Lampung City Fire Department. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The research subjects consisted of leaders and employees at the Fire Department, who were selected purposively to obtain relevant information. The results showed that the application of transformational leadership style, which includes idealized influence, inspirational motivation, and intellectual stimulation, significantly contributed to improving employee performance. This finding indicates that leaders who are able to provide role models, motivate, and encourage employee creativity can create a productive and innovative work environment. In addition, this study found that the values of integrity and empowerment of team members are key factors in improving morale and collaboration among employees. The conclusion of this study confirms the importance of implementing transformational leadership styles in organizations to achieve optimal performance, and provides recommendations for Fire Service leaders to continue developing leadership competencies for the overall success of the organization.